2021
DOI: 10.1001/jamanetworkopen.2021.40191
|View full text |Cite
|
Sign up to set email alerts
|

Association of Posttraumatic Epilepsy With 1-Year Outcomes After Traumatic Brain Injury

Abstract: IMPORTANCEPosttraumatic epilepsy (PTE) is a recognized sequela of traumatic brain injury (TBI), but the long-term outcomes associated with PTE independent of injury severity are not precisely known. OBJECTIVE To determine the incidence, risk factors, and association with functional outcomes and self-reported somatic, cognitive, and psychological concerns of self-reported PTE in a large, prospectively collected TBI cohort. DESIGN, SETTING, AND PARTICIPANTS This multicenter, prospective cohort study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
(74 reference statements)
2
28
1
3
Order By: Relevance
“…Traumatic brain injury (TBI) is a major health problem and can have a decisive impact on functional capacity and quality of life 1,2 . Epileptic seizures are a common complicatio that adds an additional burden to the challenges of TBI 3,4 . Onset of post‐traumatic seizures varies from seconds to several years after brain injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic brain injury (TBI) is a major health problem and can have a decisive impact on functional capacity and quality of life 1,2 . Epileptic seizures are a common complicatio that adds an additional burden to the challenges of TBI 3,4 . Onset of post‐traumatic seizures varies from seconds to several years after brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 Epileptic seizures are a common complicatio that adds an additional burden to the challenges of TBI. 3 , 4 Onset of post‐traumatic seizures varies from seconds to several years after brain injury. Early post‐traumatic seizures (EPTS) are usually defined as seizures occurring within the first 7 days after injury.…”
Section: Introductionmentioning
confidence: 99%
“…7 PENDEKATAN DIAGNOSIS Definisi operasional epilepsi menurut ILAE 2014, yaitu: (1) Minimal terdapat dua bangkitan tanpa provokasi atau dua bangkitan refleks dengan jarak waktu antar bangkitan pertama dan kedua lebih dari 24 jam; (2) Satu bangkitan tanpa provokasi atau bangkitan refleks dengan kemungkinan terjadinya bangkitan berulang dalam 10 tahun ke depan sama dengan bila terdapat 2 bangkitan tanpa provokasi atau bangkitan refleks; (3) Diagnosis sindrom epilepsi sudah ditegakkan. 21 Diagnosis epilepsi pasca-trauma kapitis dapat ditegakkan terutama dari anamnesis didukung pemeriksaan fisik dan penunjang. Perlu digali riwayat cedera kepala, dan tanda-tanda neurologis fokal atau difus yang berhubungan dengan bangkitan.…”
Section: Diagnosis Anamnesisunclassified
“…PTE accounts for 10–20% of acquired epilepsy in the general population and it is reported that between 4 and 50% of individuals with TBI develop PTE ( Degrauw et al, 2018 ; Tubi et al, 2019 ; Pease et al, 2022 ). PTE diagnosis is also associated with heightened morbidity and mortality ( Burke et al, 2021 ; Karlander et al, 2022 ; Ngadimon et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%